The improvement and simulation of LEACH protocol for WSNs - Zhiyong Peng; Xiaojuan Li (2010 IEEE International Conference on Software Engineering and Service Sciences, 2010)
In wireless sensor networks, the power resource of each sensor node is limited. Minimizing energy dissipation and maximizing network lifetime are important issues in the design of routing protocols for sensor networks. In this paper, Cluster routing protocol LEACH (Low-Energy Adaptive Clustering Hierarchy) is research and improved. We extend LEACH stochastic cluster-head selection algorithm via changing the round time According to the situation of sensor network. It is named Variable-round LEACH. The result simulated in NS2 shows that the energy is significantly reduced and the lifetime of the whole network is increased compared with the previous routing algorithm for the sensor networks.